Identification of Rhodamine B on the Sale Cake ku In market Agung Village Peninjoan Denpasar - Ni Kadek Era Indrayani; Didik Setiawan; Putu Gede Subhaktiyasa (Stikes Wira Medika Bali, 2017)
Snacks or cakes are ready-to-eat foods whose ingredients are made from glutinous rice flour and processed by food producers as ready-to-eat food for sale to the general public. Generally cakes sold added food additives, the use of food additives can be positive and negative (harmful) for the community. One of the dangerous food additives is the Rhodamin B dye. The purpose of this research is to identify Rhodamine B on cake Ku sold at Pasar Agung Peninjoan Village. Method: using Thin Layer Chromatography (TLC). Result: The identification shows the Rf price of the five samples 0.58, while the standard Rf is 0.70. Because the difference of Rf sample to the standard is less than 0.2. Discussion:the five positive samples contain Rhodamine B. It is recommended to the public to always be careful in consuming food, because foods containing Rhodamine B are not good for health